Monogenoidea (Polyonchoinea: Dactylogyridae) parasitizing the gills of marine catfish (Siluriformes: Ariidae) inhabiting the Atlantic Amazon Coast of Brazil - Domingues, Marcus V.; Soares, Geusivam B.; Watanabe, Alana (Zootaxa, 2016)
A parasitological survey of monogenoids infesting the gills of marine catfish (Ariidae) captured from the Atlantic coastal region of the Amazon Basin was carried out during the 2011–2013 period. The gills of 448 specimens involving twelve ariid species (29 Amphiarius rugispinis (Valenciennes), 52 Aspistor quadriscutis (Valenciennes), 74 Bagre bagre (Linnaeus), 16 Cathorops arenatus (Valenciennes), 13 Cathorops agassizii (Eigenmann & Eigenmann), 17 Cathorops spixii (Agassiz), 3 Cathorops sp., 13 Notarius grandicassis (Valenciennes), 14 Sciades couma (Valenciennes), 64 Sciades herzbergii (Bloch), 48 Sciades parkeri (Traill), 13 Sciades passany (Valenciennes), 92 Sciades proops (Valenciennes) were sampled. No monogenoids were found in Cathorops agassizi, Cathorops arenatus, Cathorops spixii, Cathorops sp. and Sciades parkeri, but the gills of the other sampled species were parasitized by at least one species of monogenoid. We identified four new species of Chauhanellus and one new species of Hamatopeduncularia: Chauhanellus hamatopeduncularoideum n. sp. from Amphiarius rugispinis and Sciades couma; Chauhanellus hypenocleithrum n. sp. from Sciades proops; Chauhanellus susamlimae n. sp. from Sciades herzbergii and Sciades passany; Chauhanellus velum n. sp. from Sciades couma, Sciades herzbergii and Sciades passany; and Hamatopeduncularia cangatae n. sp. from Aspistor quadriscutis and Notarius grandicassis. Four previously described species were reported for the first time parasitizing ariids from Atlantic Amazon: Chauhanellus neotropicalis Domingues & Fehlauer, 2006 from Amphiarius rugispinis, Aspistor quadriscutis, Notarius grandicassis and Sciades passany; Chauhanellus boegeri Domingues & Fehlauer, 2006 from Sciades couma and Sciades herzbergii; Hamatopeduncularia bagre Hargis, 1955 from Bagre bagre; and Neomurraytrematoides proops Zambrano & Añez 1993 from Sciades passany. The monotypic Neomurraytrematoides Zambrano & Añez 1993 was placed in synonymy with Neotetraonchus Bravo-Hollis, 1968 and its type-species, Neomurraytrematoides proops Zambrano & Añez 1993 was transferred to Neotetraonchus as Neotetraonchus proops (Zambrano & Añez 1993) n. comb. The morphology of the haptoral structures supports the transfer of Rhamnocercus seenghali Kumar, 2013 to Chauhanellus as Chauhanellus seenghali (Kumar, 2013) n. comb.